I am Lifted Above the World: utilizing VR for stress reduction among perinatal women of color - Blanc, Judite; Scaramutti, Carolina; Carrasco, Mary; Dimanche, Stacyca; Hollimon, Laronda; Moore, Jesse; Moise, Rhoda; Gabbay, Vilma; Seixas, Azizi (Frontiers in Psychiatry, 2024)
Background: Perinatal mental health conditions affect 800,000 individuals annually in the United States and are a leading cause of complications in pregnancy and childbirth. However, the impact of these conditions varies across racial and ethnic groups. Portable digital solutions, such as mobile apps, have been developed for maternal mental health, but they often do not adequately cater to the needs of women of color. To ensure the effectiveness and equity of these interventions, it is crucial to consider the unique experiences of perinatal women from diverse racial backgrounds. This qualitative study aims to explore the complex aspects of motherhood, maternal mental wellbeing, and resilience among perinatal women of color. It also investigates the factors that either hinder or facilitate the use of Virtual Reality (VR) for stress management in this specific demographic.: This research involves two focus groups comprising perinatal women, primarily identifying as Black or Latina, enrolled in the ongoing Nurturing Moms study at the University of Miami Miller School of Medicine. Additionally, feedback is collected from five different participants. The study assesses NurtureVR, a VR-based program integrating mindfulness techniques, relaxation exercises, and guided imagery for pregnancy and postpartum. Results: Qualitative analysis uncovers five primary themes and 19 sub-themes, addressing the complexities of motherhood, maternal mental health, attitudes towards VR therapy, postpartum care, and the perception of resilience. Participants share challenges related to household management, caregiving, financial stress, breastfeeding, relaxation, sleep, and the significance of social support. Their preferences and reservations regarding VR therapy are also expressed. Conclusion: This study sheds light on the diverse struggles and obstacles faced by women of color during and after pregnancy, with potential repercussions for their mental and sleep health. It underscores the need for mental health screening and analysis of maternal stress-related sleep issues, in addition to the facilitation of social support in maternal health programs. Additionally, it highlights the promise of culturally responsive behavioral treatments, including VR interventions, in offering timely and tailored mental health support to perinatal women, taking into account their intersectional identities.